ANTIMALARIAL DRUGS IN THERAPY OF SYSTEMIC LUPUS ERYTHEMATOSUS: PAST, PRESENT, FUTURE - Tatyana Andreyevna Lisitsyna; N M Kosheleva (Современная ревматология, 2010)
The data available in the literature on experience in using antimalarial drugs in the treatment of systemic lupus erythematosus are summarized. A major emphasis is placed on therapy with hydroxychlorochine (plaquenil) versus chlorine. Possible mechanisms of action of the drug and its effect on the course of the disease itself and concomitant abnormalities are described. Data on the toxicity of the drug and its safe use in pregnancy and lactation are also discussed